Cerebrovascular Autoregulation in Preterm Infants During and After Surgical Ligation of the Ductus Arteriosus, a Comparison Between Two Surgical Approaches - Kooi, Elisabeth M. W.; van der Laan, Michelle E.; Accord, Ryan E.; Roofthooft, Marcus T. R.; Aries, Marcel J.; Elting, Jan Willem J. (Frontiers in Pediatrics, 2020)
Objective: During ligation of the ductus arteriosus, cerebrovascular autoregulation (CAR) may deteriorate. It is unknown whether different surgical approaches affect changes in CAR differently. The objective of this study was to compare the potential change in CAR in preterm infants during and after ligation comparing two surgical approaches: sternotomy and posterolateral thoracotomy. Design: This was an observational cohort pilot study. Setting: Level III NICU. Patients: Preterm infants (GA < 32 weeks) requiring ductal ligation were eligible for inclusion. Interventions: Halfway the study period, our standard surgical approach changed from a posterolateral thoracotomy to sternotomy. We analyzed dynamic CAR, using an index of autoregulation (COx) correlating cerebral tissue oxygen saturation and invasive arterial blood pressure measurements, before, during, and after ligation, in relation to the two approaches. Measurements and Main Results: Of nine infants, four were approached by thoracotomy and five by sternotomy. Median GA was 26 (range: 24.9–27.9) weeks, median birth weight (BW) was 800 (640–960) grams, and median post-natal age (PNA) was 18 (15–30) days, without differences between groups. COx worsened significantly more during and after thoracotomy from baseline (Δρ from baseline: during surgery: Δ + 0.32, at 4 h: Δ + 0.36, at 8 h: Δ + 0.32, at 12 h: Δ + 0.31) as compared with sternotomy patients (Δρ from baseline: during surgery: Δ + 0.20, at 4 h: Δ + 0.05, at 8 h: Δ + 0.15, at 12 h: Δ + 0.11) (F = 6.50; p = 0.038). Conclusions: In preterm infants, CAR reduced significantly during and up to 12 h after ductal ligation in all infants, but more evident during and after posterolateral thoracotomy as compared with sternotomy. These results need to be confirmed in a larger population.